Atrocities against Religious Minorities of Bangladesh: Can we Address it as Genocide? - Oikya, Upal Aditya (Pécs journal of international and European law, 2020)
The sufferings of religious minorities of Bangladesh through state practice and private measures are not unknown to the international community. In the name of religion, they often become the victim of many discriminations and human rights violations. Can we term these discriminations and human rights violations as ‘genocide’? To identify this academic debate, this paper will go through the international legal instruments as well as other municipal legal statutes to see howthey have defined genocide. Finally, this paper will try to venture into a definition of genocide to address these discriminations and human rights violations which are being committed against the religious minorities of Bangladesh.